The miR-143/-145 cluster regulates plasminogen activator inhibitor-1 in bladder cancer - Villadsen, S B (Nature Publishing Group, 2012)
BACKGROUND: Upregulation of the proto-oncogene plasminogen activator inhibitor-1 (PAI-1) is a common hallmark of various solid tumours, but the mechanisms controlling its expression are not fully understood. METHODS: We investigate microRNAs (miRNAs) regulating PAI-1 in a panel of normal bladder urothelial biopsies, superficial Ta bladder tumours and invasive T1–T4 tumours using expression microarrays and qRT–PCR. The prognostic implications of PAI-1 deregulation are established by tissue microarray staining of non-muscle-invasive bladder tumours. MicroRNA repression of PAI-1 is assayed by ectopic miRNA expression, argonaute immunoprecipitation and luciferase assays. RESULTS: We found that the miR-143/-145 cluster is downregulated in all stages of bladder cancer and inversely correlated with PAI-1 expression. Mature miR-143 and miR-145 are coordinately expressed, and both directly target the PAI-1 3′UTR, leading to reduced PAI-1 mRNA and protein levels. Furthermore, we show that PAI-1 and miR-145 levels may serve as useful prognostic markers for non-muscle-invasive bladder tumours for which accurate progressive outcome is currently difficult to predict. CONCLUSION: This report provides the first evidence for direct miRNA regulation of PAI-1 in bladder cancer. We also demonstrate mRNA co-targeting by a cluster of non-family miRNAs, and suggest miR-145 and PAI-1 as clinically relevant biomarkers in bladder cancer.